The dispute between Malaysia and Indonesia over the ND6 and ND7 sea blocks: a Malaysian perspective - Torla, Areej; Yusof, Salma; Mohd Kamal, Mohd Hisham (2015)
Malaysian has Asserted sovereign rights over the ND^ and ND7 sea blocks, which paartially overlap with the Ambalat sea blocks. Indonesia has also asserted sovereign rights over there. This article argues the validity of Malaysia's claim over the ND6 and ND7 sea blocks by virtue of the Pulau Ligitan and Pulau Sipadan case in which the International Court of Justice found that the 4 10' N parallel mentioned in the 1891 Convention between Great Britain and the Netherlands Defining Boundaries in Borneo terminated on the east cost of Sebatik and did not extend seawards. This article finds that Malaysia may use the Sipadan and Ligitan Island as a basic assert sovereign rights over the DN6 and ND7 sea blocks. The authors also highlights several other documents including a 1954 British declaration and bilateral treaties between Malaysia and Indonesia